Aetiological investigation of sensorineural hearing loss in children. Issue 3 (21st February 2005) - Wilson, C; Roberts, A; Stephens, D
Abstract : A survey of aetiological investigations arranged on children with severe/profound bilateral sensorineural hearing impairment by ENT consultants and community paediatricians working in audiology is described. Greater routine use of ECG, urine analysis, and ophthalmological assessment is needed, with a more selective approach to other investigations as recommended by the British Association of Audiological Physicians (BAAP) and the British Association of Community Doctors in Audiology (BACDA).